Der Schumpetersche Unternehmer in der Geschichte des ökonomischen Analyse - Hans Frambach (University of Wuppertal, Schumpeter School of Business and Economics, 2018)
Schumpeter's book History of Economic Analysis (1954) is not only a famous and seminal contribution to the field of the history of economic thought, it also embodies Schumpeter's unique way of treating economic thought, which sometimes makes the term history of economic analysis appear as being almost synonymous to the book title. The connection between the History of Economic Analysis and the Schumpeterian entrepreneur is analysed, and according to this the hypothesis to what extent does Schumpeter with his idea of the entrepreneur - which surely reveals some parallels to his own personality - appear in his style of writing economic analysis is developed.
urn:nbn:de:hbz:468-20180606-093358-9
Keywords: 330